Retinal multimodal-imaging and functional tests in a mitochondrial disease with focal and segmental glomerulosclerosis - Xiao-Hong Liu; Xi Shen; Yi-Sheng Zhong (International Journal of Ophthalmology)
The phenotypes of the adenine-to-guanine transition at position 3243 of mitochondrial DNA (m.3243A>G) are highly variable, with different symptoms observed in different patients. These include mitochondrial encephalomyopathy, lactic acidosis, and stroke-like episodes (MELAS); maternally inherited diabetes and deafness syndrome (MIDD); other syndromic conditions; or non-syndromic mitochondrial disorders. Renal involvement associated with this mutation generally manifests as subnephrotic proteinuria, progressive deterioration of kidney function, and increased morbidity. The retinopathies linked to the m.3243A>G mutation have heterogeneous presentations, characterized by variable degrees of retinal pigment epithelium (RPE) atrophy and hyperpigmentation at the posterior pole. As a severe phenotype of the m.3243A>G mutation, MELAS combined with focal and segmental glomerulosclerosis (FSGS) is rare. We herein firstly reported in detail the ophthalmic manifestations of a patient with this condition. Additionally, we reviewed the literature on fundus, ophthalmic electrophysiology, and optical coherence tomography (OCT) findings related to the m.3243A>G mutation.